2019
DOI: 10.1590/1806-9282.65.2.183
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemistry and histopathological study of ankaferd blood stopper in a rat model of cervical inflammation

Abstract: SUMMARY OBJECTIVE: Ankaferd Blood Stopper (ABS) is a medicinal plant extract used topically as a hemostatic, anti-inflammatory, and anti-oxidant agent. Its cytoprotective effect mainly depends on its pleiotropic properties by modulating inflammatory mediators such as IL-1β, IL-6, and TNF-α. This study aims to test the possible therapeutic effect of ABS in the treatment of erosive and inflammatory conditions occurring in the uterine cervix. METHODS: Twenty-four female Wistar Albino rats were used in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the pathophysiological mechanism of the occurrence and development of cervicitis, the release of a variety of inflammatory factors has become an important risk factor in the development of cervicitis 19 . CP and CRP in the model group increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathophysiological mechanism of the occurrence and development of cervicitis, the release of a variety of inflammatory factors has become an important risk factor in the development of cervicitis 19 . CP and CRP in the model group increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dynactin, EGR-1, Midkine, NF-1, Twinfilin, V-Myc, and YY1 (Yin Yang 1) can contribute both the anti-inflammatory and tissue-healing effects of ABS with various mechanisms [46] . Studies also highlight the potential benefits of ABS in numerous distinct inflammatory conditions related to the oral mucosa, intestinal mucosa, cartilage tissue, liver, pericardium, cervix and uterus [19] , [47] , [48] , [49] , [50] , [51] .…”
Section: Evaluation and Discussion Of The Hypothesismentioning
confidence: 99%
“…In a study by Büyüktiryaki et al, ABS decreased the intestinal necrosis in a necrotizing enterocolitis rat model [28]. Beyazit et al reported that ABS reduced inflammation in the developed cervicitis rat model [29]. However, no significant positive effect of ABS was observed on sciatic nerve injury and tendon healing [30,31].…”
Section: Discussionmentioning
confidence: 99%